Glioblastoma multiform with primitive neuronal component, radiological and histology features: a case report - Santiago Valbuena (SpringerOpen, 2021)
Abstract Background Glioblastoma multiform with primitive neuronal component (GBM-PNC) has been recently defined as a rare variant of glioblastoma multiform (GBM), which shows characteristically pathological pattern of less differentiated areas with small blue cell morphology and neuroectodermic immunophenotype. New studies emphasize its characteristics and differences, which have become vitally important due to the changes in therapeutic management. Case presentation We present the case of 57-year-old male patient who onset symptoms were secondarily widespread partial seizures and expression aphasia. Brain magnetic resonance imaging (MRI) reported left enhanced temporal infiltrating lesion, requiring surgery twice throughout two years. At first surgery, pathological samples revealed embryonic tumor of the central nervous system (grade IV, WHO 2016), so PACKER protocol consisting of CSRT (craniospinal radiation) plus weekly vincristine followed by 8 cycles of cisplatin, lomustine and vincristine usually used for medulloblastomas or other primitive neuroectodermal tumors was started. However, due to reappearance of symptoms and progression in MRI, reoperation was performed with definitive diagnosis of GBM-PNC (Grade IV, WHO 2016) and switched to STUPP protocol. Conclusions It is important to take into account the chance of this entity when histological, radiological and intraoperative findings orient toward a primitive neural tumor since the presence of GBM could be overlooked leading to mistakes in diagnosis and the therapeutic orientation.